ENFORCEMENT OF THE LAW AGAINST THE PROPAGATION OF INFORMATION THAT INCITES HATRED OR INDIVIDUAL HOSTILITY BASED ON ETHNIC, RELIGIOUS, RACIAL, AND INTER-GROUP THROUGH SOCIAL MEDIA - Berlian, Arthur tahta (Progressive Law Review, 2020)
In a community life it is undeniable that conflicts can happen anywhere, by anyone, and at any time. The conflict occurs for any reason both least and the greatest and sometimes difficult to solve. In conflict situations, there can be conflicts between individuals, conflicts between groups, and even more complex conflicts, such as conflicts between tribes, religion, race, and inter-group that are subsequently in brief (SARA). The problem raised in this research is why perpetrators commit a criminal offence dissemination of electronic information containing the issue of SARA, how to apply criminal sanctions against perpetrators who spread the issue of SARA through social media based on prevailing laws and regulations, and how judgment of judges against perpetrators of dissemination of information containing the issue of SARA through electronic media. The results of the study showed that the causes of criminal issues spread to the issue of the perpetrators is the hatred of the Lampung people, because the perpetrator has had a dispute understanding of someone who is in Lampung. Differences of thought, disputes between individuals and groups is often the case, but do not necessarily blaspheme, overtake, and harasses with profanity phrases. Social Media was created for the means of communication and not for the event of the blasphemy.